The evolution of species abundances in terrestrial vertebrates. (22nd September 2021) - Pie, Marcio R.; Caron, Fernanda S.; Divieso, Raquel
Abstract: Interspecific differences in species abundances are one of the oldest and most universal patterns in ecology, yet little is known about how these differences are generated over evolutionary time. In this study, we test whether there is evidence for phylogenetic signal in population densities of four large groups of terrestrial vertebrates, namely birds, mammals, amphibians, and squamates. In addition, we test the hypothesis that the relative number of species in a clade might be a predictor of the abundance of its constituent species. However, given that the number of species in a clade is the outcome of both its age and diversification rate, and each of these factors was tested separately. Our results provide strong support for phylogenetic signal in species densities for all clades, regardless of differences in how species density was computed, or phylogenetic uncertainty. On the other hand, there was no evidence for a relationship between species abundance and the diversity of its encompassing clade. The implications of phylogenetic signal are discussed in the context of models of species abundance distributions, including Hubbell's neutral theory of biodiversity and biogeography. Abstract : To better understand how interspecific differences in species abundances are generated over evolutionary time, we tested whether there is evidence for phylogenetic signal in population densities of terrestrial vertebrates and found strong evidence for this hypothesis. We also assessed whether the relative number of species in a clade might be a predictor of the abundance of its constituent species, testing separately both its age and diversification rate, but there was no evidence for this relationship.